An Introduction to Method of Theory Building in Integrative Criminology - Hossein Gholami; hossein javadi hossein abadi (روش شناسی علوم انسانی, 2019)
Contemporary crime analysts aside from modern paradigms have now postmodern views and quantum paradigms to view the future of criminology in reconciling theories, regardless of the theoretical ones. The third generation of criminology, i.e., Integrative criminology, was born to align the criminology of the main and critical flow, develop criminological theories, discover new concepts, provide comprehensive comprehension of crime, eliminate unrealistic contradictions, and organize dispersed theories. Convergent criminology seeks to improve the theories’ efficiency and concepts by integrating a set of concepts or propositions in them. Although this approach has become a common paradigm for postmodern criminology, some of the criminologists still oppose this theorizing method due to the lack of a clear framework and roadmap for building an integrated theory of criminology. Removing the mentioned gap requires identifying the exact definition of this approach and recognizing the basic features, typology, and goals of the integrated theory. In this way, it will be possible to provide a template for the creation of integrated theories in the field of criminology. The present paper, while addressing the aforementioned issues, proposes a model that considers the basic assumptions of the theories and accordingly and identifies the method (conceptual or propositional integration), the level (micro, macro), and appropriate scope of the integration. Therefore, it will be a guide for theorists in constructing an integrated theory.